Front Cover: Photoredox Allylation Reactions Mediated by Bismuth in Aqueous Conditions (Eur. J. Org. Chem. 11/2021). Issue 11 (5th March 2021) - Potenti, Simone; Gualandi, Andrea; Puggioli, Alessio; Fermi, Andrea; Bergamini, Giacomo; Cozzi, Pier Giorgio
Abstract : The Front Cover shows a Dream Wedding! Bismuth and photoredox catalysis get married in this photoredox allylation reaction of aldehydes in aqueous solvent. The green reaction conditions (organic photoredox catalyst, available and not toxic metal, aqueous solvent) employed and the broad scope open new perspectives in the field of photoredox radical to polar cross over reactions. The profile of a well know Italian town on water is in the skyline. Where celebrate a better wedding? More information can be found in the Communication by G. Cozzi et al.